The Effect Of Firm Size, Profitability, And Debt Policy On Firm Value In Transportation Companies Listed On The Indonesia Stock Exchange (IDX) For The 2020-2022 Period - Clarita Angel; Charles Charles; Arie Pratania Putri; Rohima Br Purba (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The government has established and expanded transportation companies to improve public efficiency. Various actions have been taken by the government to support the growth of the transportation sector due to the high demand from society. Large companies have the potential to achieve more cost-effective offers in vehicle transactions or large-scale fuel purchases. High profitability opens opportunities for companies to become more stable and competitive in a highly competitive market environment. Transportation companies also require funds to improve infrastructure and develop technology through debt. This study aims to examine the impact of firm size, profitability, and debt policy on the value of companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. Firm size is measured by total assets, profitability by return on assets (ROA), and debt policy by the debt to equity ratio (DER) and debt to assets ratio (DAR). The firm value is analyzed using the price to book value (PBV), which reflects market perception of the company's prospects and performance. The data used in this study is secondary data obtained from financial reports of companies listed on the IDX during 2020-2022. The sample consists of 11 companies that meet the inclusion criteria. The analysis technique used is multiple linear regression to test the effect of independent variables (firm size, profitability, and debt policy) on the dependent variable (firm value). The results of the study show that the independent variables do not have a significant effect on firm value. According to theory, this study suggests that these internal factors do not have enough influence in shaping market perceptions of company value in the Indonesian capital market.